Probing new classes of π-acceptor ligands for rhodium catalyzed hydroformylation of styrene - Breit, Bernhard (Journal of molecular catalysis. A, Chemical, 1999)
Three hitherto unexplored classes of strong π-acceptor ligands for use in homogeneous catalysis—phospha-π-aromatic compounds (class A), pyrrolyl phosphines (class B) and phosphenium cations (class C)—have been evaluatated for rhodium catalyzed hydroformylation of styrene. When testing monodentate ligands, the ortho/ortho′-disubstituted phosphabenzene derivative 1b provided a rhodium-catalyst endowed with the highest catalytic activity. Based upon these results a first series of bidentate phosphabenzene ligands have been tailored employing the concept of an electronic differentiation of the two binding sites. An oxazoline/phosphabenzene system 8 which is capable of forming an eight-membered chelation ring gave the best results. Thus, a quantitative conversion of styrene at ambient temperature afforded the desired 2-phenylpropanal in high regioselectivity (25:1).
Gesehen am 21.03.2018